PENDAMPINGAN PERSIAPAN KERJA BAGI MAHASISWA TINGKAT AKHIR VOKASI KAMPUS WATES DI MASA ADAPTASI KEBIASAAN BARU - Wisataone, Voettie; Rosidah, Rosidah; Sasmita Wijayanti, Nadia; Hanafi, Mochamad (Jurnal Abdimas Adpi Sosial dan Humaniora, 2021)
This Community Service Activity aims to provide insight and provision to final-level vocational students at the Wates campus, Kulon Progo, Yogyakarta. The activities include; online seminars and mentoring in making curriculum vitae, job application letters, and preparing for online interviews. The activity was carried out through three stages of activity, namely preparation, implementation and evaluation. Preparation is carried out by conducting a needs survey for final year students regarding work preparation. The implementation is carried out by training and mentoring, using the lecture method, namely through organizing online seminar activities through the Zoom application entitled "Preparing for the world of work in the New Normal era", followed by question and answer discussions and training and mentoring as a form of implementing the training that has been provided. Evaluation of activities is carried out for each stage through data collection from each stage of activity. The method used in this stage of community service implementation includes seminars and mentoring. This method provides an opportunity to equip trainees to prepare for work in a period of adapting to new habits which include self-development and work readiness ethics, how to see job opportunities in the pandemic era, making creative CVs and job applications, and tips on preparing for job interviews via online.